Use of deferred consent for severely ill children in a multi-centre phase III trial - Boga Mwamvua (Trials, 2011)
Abstract Background Voluntary participation of a subject in research respects a subject's rights, strengthens its ethical conduct, and is formalized by the informed consent process. Clinical trials of life-saving interventions for medical emergencies often necessitate enrolment of patients where prior written individual informed consent is impossible. Although there are regulations and guidelines on protecting subjects in emergency research, these have been criticised for being limited and unnecessarily restrictive. Across Europe and the United States stringent regulations have resulted in a substantial decline of clinical trials involving emergency interventions. Methods We are conducting a trial of fluid resuscitation in children with hypovolaemic shock in six hospitals across three malaria-endemic African countries. The design is pragmatic as children are enrolled on clinical criteria alone and is being conducted in hospitals with facilities typical of many district hospitals across Africa. The trial aims to inform strategy for managing children with febrile illness and features of shock. In order to develop appropriate consent processes for the trial, we conducted a narrative review of current international recommendations for emergency consent. Results Practical or specific guidance was generally sparse or confusing with few examples in the literature to direct our informed consent process. For a sub-group of children who were critically sick or where parents themselves were otherwise too distressed to consider prior written consent, we opted for a modified form of deferred consent. This included verbal assent from guardians at the point of enrolment, with full written consent obtained after stabilising the child. For children who died prior to full written consent, ethical permission was received to waiver full consent. Conclusions In light of the controversy around guidance and regulations in this area we report how and why we have used a modified system of deferred consent in an emergency intervention trial in children. Although approved by all relevant ethics committees and operational in 3 countries in Africa, formal research is now necessary to explore the perceptions and experiences of parents, health workers, researchers and ethics committees of the modified method of deferred consent.